1999
DOI: 10.1161/01.cir.100.19.1958
|View full text |Cite
|
Sign up to set email alerts
|

Independent Prognostic Value of Elevated C-Reactive Protein in Unstable Angina

Abstract: In unstable angina, CRP is a strong independent marker of increased 90-day risk. Compared with CRP at admission, CRP at discharge is better related to later outcome and could be of great utility for risk stratification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
114
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 199 publications
(123 citation statements)
references
References 22 publications
3
114
0
6
Order By: Relevance
“…Several epidemiological studies have identified IL-6 and C-reactive protein (CRP) as predictors of general morbidity in the elderly. 4 IL-6 and CRP are prognostic factors in unstable angina 5,6 and are associated with cardiovascular and all-cause mortality. 7 Visser et al showed in a large epidemiological study that overweight adults have constitutively elevated serum CRP concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Several epidemiological studies have identified IL-6 and C-reactive protein (CRP) as predictors of general morbidity in the elderly. 4 IL-6 and CRP are prognostic factors in unstable angina 5,6 and are associated with cardiovascular and all-cause mortality. 7 Visser et al showed in a large epidemiological study that overweight adults have constitutively elevated serum CRP concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Nineteen studies were selected; 15 were carried out by North American or European groups 1,[14][15][16][17][18][19][20][21][22][23][24][25][26][27] , three by Brazilian groups [28][29][30] and one by an Argentinean group 31 . All these studies were published in journals with an impact factor ≥ 3, except for two Brazilian studies 28,29 .…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
“…The sample size of the studies increased throughout the years, ranging from 32 to 7,108 patients (mean of 1,123 ± 1,674); seven studies had more than 1,000 patients 20,21,[23][24][25][26][27] , in a total of 21,339 patients studied. C-reactive protein was measured in all studies by means of a high-sensitivity method; 11 used nephelometry [14][15][16][17][18][19][21][22][23][24]26,[28][29][30] , three used turbidimetry 1,25,27 , one used luminometry 20 , and two used ELISA (Enzyme Liked Immunosorbent Assay) 31 .…”
Section: Characteristics Of the Studiesmentioning
confidence: 99%
See 2 more Smart Citations